3 - Acculturation and Botswana Migrant Miners in South Africa, 1930–1980 - Wazha G. Morapedi, (Afrika Zamani, 2022)
This paper analyzes the acculturation of Botswana mine migrants who worked in the South African mines between 1930 and 1980. It shows how the compound mine system affected Botswana cultural practices. The study argues that some Botswana men ended up living permanently in South Africa and taking up the languages and cultural practices of South Africans and they came to be known in Botswana as Makgweelwa. However, the paper reveals that Botswana men kept contact with their families and relatives back home and that complete acculturation was not pronounced. It argues that Botswana men in the South African mines maintained their language and cultural practices, and that no dominant language existed in the compounds. The compound system also helped lessen acculturation because men were housed separately according to their ethnicities.